On the extension of Newton’s second law to theories of gravitation in curved space-time - Arminjon, M. (Archives of Mechanics, 1996)
We investigate the possibility of extending Newton’s second law to the general framework of theories in which special relativity is locally valid, and in which gravitation changes the flat Galilean space-time metric into a curved metric. This framework is first recalled, underlining the possibility to define uniquely a space metric and a local time in any given reference frame, hence to define velocity and momentum in terms of the local space and time standards. lt is shown that a unique consistent definition can be given for the derivative of a vector (the momentum) along a trajectory. Then the possible form of the gravitation force is investigated. lt is shown that, if the motion of free particles has to follow space-time geodesics, then the expression for the gravity acceleration is determined uniquely. lt depends on the variation of the metric with space and time, and it involves the velocity of the particle.